Applied ASP.NET 4 in context - Freeman, Adam (The expert's voice in .NET., 2011)
Applied ASP.NET 4 in Context answers the commonly asked question, Yes, but how does it work in reality? Through a series of carefully constructed examples, the book shows how ASP.NET works in a real-world context, showing how technologies and best practices can be drawn together to create well-crafted web applications.